Estrogen Therapy Worsens Cardiac Function and Remodeling and Reverses the Effects of Exercise Training After Myocardial Infarction in Ovariectomized Female Rats - Almeida, Simone Alves de; Claudio, Erick R. G.; Mengal, Vinicius; Brasil, Girlandia A.; Merlo, Eduardo; Podratz, Priscila L.; Graceli, Jones B.; Gouvea, Sonia A.; Abreu, Gláucia Rodrigues de (Frontiers in Physiology, 2018)
There is an increase in the incidence of cardiovascular events such as myocardial infarction (MI) after menopause. However, the use of oestrogen therapy (E2) remains controversial. The aim of this study was to evaluate the effects of E2, alone and combined with exercise training (ET), on cardiac function and remodelling in ovariectomised (OVX) rats after MI. Wistar female rats underwent ovariectomy, followed by MI induction were separated into 5 groups: S; MI; MI+ET; MI+E2 and MI+ET+E2. Fifteen days after MI or sham surgery, treadmill ET and/or oestrogen therapy (17-ß oestradiol-3-benzoate (E2), s.c. three times/week) were initiated and maintained for eight weeks. After the treatment and/or training period, the animals underwent cardiac haemodynamic evaluation through catheterisation of the left ventricle (LV); the LV end systolic and diastolic pressures (LVESP and LVEDP, respectively), maximum LV contraction and relaxation derivatives (dP/dt+ and dP/dt-), and isovolumic relaxation time (Tau) were assessed. Moreover, histological analyses of the heart (collagen and hypertrophy), cardiac oxidative stress (advanced oxidation protein products, AOPP), pro- and antioxidant protein expression by Western blotting and antioxidant enzyme activity in the heart were evaluated. The MI reduced the LVESP, dP/dt+ and dP/dt- but increased the LVEDP and Tau. E2 did not prevent the MI-induced changes in cardiac function, even when combined with ET. An increase in the dP/dt+ was observed in the E2 group compared with the MI group. There were no changes in collagen deposition and myocyte hypertrophy caused by the treatments. The increases in AOPP, gp91-phox, and angiotensin II type 1 receptor expression induced by MI were not reduced by E2. There were no changes in the expression of catalase caused by MI or treatment, although, a reduction in SOD expression occurred in the groups subjected to E2 treatment. Whereas there were post-MI reductions in activities of superoxide dismutase (SOD) and catalase enzymes, only that of SOD was prevented by ET. Therefore, we conclude that E2 therapy does not prevent the MI-induced changes in cardiac function and worsens parameters related to cardiac remodelling. Moreover, E2 reverses the positive effects of ET when used in combination, in ovariectomised infarcted female rats.